Development of a key performance indicator system to benchmark relative paratransit performance - Morse,L; Trompet,M; Barron,A; Graham,DJ (Transportation Research Record-Series, 2017)
The Americans with Disabilities Act of 1990 prohibits discrimination against people with disabilities. US transit agencies are therefore required to offer services to eligible customers that complement the mobility opportunities provided to the general public on fixed-route public transit. While these paratransit services are necessary and just, they represent a proportionally large cost to agencies: approximately eight times the cost per boarding compared to fixed-route bus service. To be able to identify opportunities for (cost) efficiencies, and to further improve the quality of paratransit services offered, the twenty agencies of the American Bus Benchmarking Group (ABBG) decided to benchmark their relative performance in paratransit management and operations. To ensure comparability of agencies’ performance and hence ensure the usefulness of the benchmarking program, a key performance indicator system was developed and associated data items were defined in detail. The scope of this system went beyond the data already provided to the National Transit Database, both in amount and granularity of data collected, as well as the detail of definitions. This paper describes the challenges, respective solutions, and other lessons identified during four years of paratransit benchmarking development led by Imperial College London, the ABBG facilitators. The paper provides transit agencies and authorities as well as benchmarking practitioners and academics an opportunity to apply these lessons for the further benefit of paratransit services and their customers around the U.S.